Political Conflict in the Digital Age: The Relationship Between President Joko Widodo and the “Jokowi Haters” Group Amid the Controversy Over the Fake Diploma Issue - Audrey G.D Tangkudung; Jemmy Y Kaseger; Robert Sagay (Interdisciplinary Social Studies, 2026)
This study examines political conflict in Indonesia’s digital era through the controversy surrounding President Joko Widodo’s alleged fake diploma and the emergence of the “Jokowi Haters” group. The rapid growth of social media has transformed political communication, enabling the spread of polarization, delegitimization, and identity-based conflict in online public spaces. Therefore, this research aims to analyze the development of political conflict in the digital sphere, explain the function of the fake diploma issue as a delegitimization strategy, and identify the role of social media in intensifying political polarization. This study employed a qualitative approach using a case study method. Data were collected through analysis of online news reports, social media content, legal documents, official clarifications, and relevant literature. The analysis applied social conflict theory, media framing theory, spiral of silence theory, and echo chamber theory to interpret the phenomenon comprehensively. The findings reveal that the fake diploma issue functions not merely as a legal controversy but as a political instrument used to undermine presidential legitimacy and public trust. Social media algorithms strengthen echo chambers by continuously exposing users to reinforcing narratives, while negative sentiment dominates digital discourse. In conclusion, digital political conflict in Indonesia increasingly relies on personal narratives and symbolic attacks, which threaten democratic stability, institutional trust, and constructive public debate.